Activated K‐Ras, but Not H‐Ras or N‐Ras, Regulates Brain Neural Stem Cell Proliferation in a Raf/Rb‐Dependent Manner. (21st May 2015) - Bender, R. Hugh F.; Haigis, Kevin M.; Gutmann, David H.
Abstract: Neural stem cells (NSCs) give rise to all the major cell types in the brain, including neurons, oligodendrocytes, and astrocytes. However, the intracellular signaling pathways that govern brain NSC proliferation and differentiation have been incompletely characterized to date. Since some neurodevelopmental brain disorders (Costello syndrome and Noonan syndrome) are caused by germline activating mutations in the RAS genes, Ras small GTPases are likely critical regulators of brain NSC function. In the mammalian brain, Ras exists as three distinct molecules (H‐Ras, K‐Ras, and N‐Ras), each with different subcellular localizations, downstream signaling effectors, and biological effects. Leveraging a novel series of conditional‐activated Ras molecule‐expressing genetically engineered mouse strains, we demonstrate that activated K‐Ras, but not H‐Ras or N‐Ras, expression increases brain NSC growth in a Raf‐dependent, but Mek‐independent, manner. Moreover, we show that activated K‐Ras regulation of brain NSC proliferation requires Raf binding and suppression of retinoblastoma (Rb) function. Collectively, these observations establish tissue‐specific differences in activated Ras molecule regulation of brain cell growth that operate through a noncanonical mechanism. Stem Cells   2015;33:1998–2010